2019
DOI: 10.1111/jre.12681
|View full text |Cite
|
Sign up to set email alerts
|

Biological response to peri‐implantitis treatment

Abstract: Objective To investigate biological markers of peri‐implantitis (PIP) in crevicular fluid before and after surgical and antimicrobial therapy. Material and Methods Forty‐eight participants (24 healthy implants and 24 PIP) were clinically evaluated, and peri‐implant crevicular fluid (PICF) samples were collected at baseline for both groups, and at 3‐months after surgical and antimicrobial treatment (ie, n = 21 PIP completers). Samples were analyzed for interleukin‐1β (IL‐1β), matrix metalloproteinase‐8 (MMP‐8),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 63 publications
2
23
2
1
Order By: Relevance
“…SUP was not identified in any healthy implant or exhibiting mucositis. This finding supports previous observations 9,12 . In contrast, recent data suggested that SUP can be present in mucositis that display a higher pathogenicity of microbiome compared with non‐SUP mucositis implants 23 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…SUP was not identified in any healthy implant or exhibiting mucositis. This finding supports previous observations 9,12 . In contrast, recent data suggested that SUP can be present in mucositis that display a higher pathogenicity of microbiome compared with non‐SUP mucositis implants 23 .…”
Section: Discussionsupporting
confidence: 90%
“…Few studies have addressed the prevalence of SUP 8‒10,12 . From a historical perspective, Fransson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-4, -8 and -12 showed no differences between health and PID [31]. Chemokines IL-8 and Macrophage inflammatory protein-1α (MIP-1α) were higher in diseased sites [39,40]. However, to our knowledge, these findings were not corroborated by other studies.…”
Section: Anti-inflammatory Cytokinescontrasting
confidence: 63%
“…Alongside with pro‐inflammatory markers and MMP‐8, MIP‐1α/CCL3 is a protein with chemotactic (stimulation of cell migration) properties which plays an important role in inflammation and increased activation of bone resorption cells (osteoclasts). In a study by Petković et al (2010), increased levels of MIP‐1α/CCL3 in PICF of diseased implants were found when compared to healthy implants, whereas no difference between healthy and diseased sites was found for levels of MIP‐1α/CCL3 in a more recent study by Bhavsar et al (2019). In addition to this latter study, our findings also indicate that this marker does not seem to differentiate between peri‐implant health and disease.…”
Section: Discussionmentioning
confidence: 94%